Wave Attenuation Through an Arctic Marginal Ice Zone on 12 October 2015: 1. Measurement of Wave Spectra and Ice Features From Sentinel 1A. Issue 5 (20th May 2018) - Stopa, J. E.; Ardhuin, F.; Thomson, Jim; Smith, Madison M.; Kohout, Alison; Doble, Martin; Wadhams, Peter
Abstract: A storm with significant wave heights exceeding 4 m occurred in the Beaufort Sea on 11–13 October 2015. The waves and ice were captured on 12 October by the Synthetic Aperture Radar (SAR) on board Sentinel‐1A, with Interferometric Wide swath images covering 400 × 1, 100 km at 10 m resolution. This data set allows the estimation of wave spectra across the marginal ice zone (MIZ) every 5 km, over 400 km of sea ice. Since ice attenuates waves with wavelengths shorter than 50 m in a few kilometers, the longer waves are clearly imaged by SAR in sea ice. Obtaining wave spectra from the image requires a careful estimation of the blurring effect produced by unresolved wavelengths in the azimuthal direction. Using in situ wave buoy measurements as reference, we establish that this azimuth cutoff can be estimated in mixed ocean‐ice conditions. Wave spectra could not be estimated where ice features such as leads contribute to a large fraction of the radar backscatter variance. The resulting wave height map exhibits a steep decay in the first 100 km of ice, with a transition into a weaker decay further away. This unique wave decay pattern transitions where large‐scale ice features such as leads become visible. As in situ ice information is limited, it is not known whether the decay is caused by a difference in ice properties or a wave dissipation mechanism. The implications of the observed wave patterns are discussed in the context of other observations. Plain Language Summary: Our work entitled "Wave attenuation through an Arctic marginal ice zone on 12 October 2015. 1. Measurement of wave spectra and ice features from Sentinel‐1A, " uses a newly developed method to extract wave spectra from radar imagery over sea ice. This is possible since the sea ice rapidly removes the short waves which usually distort the radar imagery. We are able to estimate thousands of wave spectra across several hundred kilometers at kilometer‐scale resolution for the first large‐scale view of wave attenuation across the marginal ice zone. Our results show a unique wave attenuation pattern described by a piecewise exponential decay that changes by a factor of 10. The transition between the different wave attenuation regions occurs near a change in sea ice conditions we estimate from the SAR backscatter. This suggests the wave‐ice interaction mechanisms are indeed changing over these large scales. Key Points: Wave spectra are retrieved from SAR Sentinel‐1A across 400 km of the marginal ice zone Strong wave attenuation is observed just inside the ice edge, with weaker decay further into the ice The transition in wave attenuation could be related to the observed changes in young sea ice conditions